THE BELT AND ROAD INITIATIVE IN MALAYSIA: A DECADE OF SHIFTS, CONTINUITY, AND RENEWED FOCUS - Tan Wooi Yee (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Since the launch of China’s Belt and Road Initiative (BRI) in 2013, Malaysia has been an active and pragmatic partner, leveraging the initiative for infrastructure development and economic growth. Existing literature on the BRI in Malaysia primarily focuses on high-profile projects such as the East Coast Rail Link (ECRL), Forest City, and the Malaysia-China Kuantan Industrial Park. However, this narrow focus overlooks the broader, multidimensional impact of the BRI in Malaysia. This article addresses this gap by analysing Malaysia’s BRI engagement through the lens of the five key connectivity areas: policy coordination, infrastructure connectivity, unimpeded trade, financial integration, and people-to-people exchange. The analysis reveals that Malaysia-China cooperation under the BRI made substantial progress across all five areas before 2018. However, subsequent political changes led to policy adjustments that disrupted the implementation of major projects, particularly the ECRL, and strained Malaysia-China bilateral relations. The COVID-19 pandemic later served as a catalyst for renewed diplomatic engagement, with joint efforts in aid distribution and vaccine cooperation helping to restore relations. Under the current Anwar administration, Malaysia remains committed to the BRI while emphasizing "high-quality cooperation" in emerging sectors such as the digital economy and renewable energy. Three critical factors explain the BRI’s relative success in Malaysia: (1) the strong historical bilateral relationship between Malaysia and China, (2) Malaysia’s pragmatic approach in aligning the BRI with its national development goals, and (3) the strategic use of BRI partnerships by Malaysian elites to bolster political legitimacy. Through a comprehensive assessment of the BRI achievements in Malaysia, this study provides a broader understanding of how Malaysia navigates its participation in China’s global development strategy.